Optimal high-rigidity structure design for CNC machine tools using CAE technique. Issue 8 (28th October 2014) - Wang, Kun-Chieh
Abstract : Purpose: – For machine tools, the machining performance is mainly determined by the rigidity of the machine structure. How to design a machine tool with high rigidity is always a challenge issue. The paper aims to discuss these issues. Design/methodology/approach: – In this paper, the Computer Aided Engineering (CAE) technique is used to analyze the structure rigidity of a Computer-Numerical Control (CNC) turn-mill machining center. The considered structure parameters include static rigidity and vibration mode. Through the integral analyses of these two structure parameters in conjunction with the practical design experiences, an optimal structure is obtained. Findings: – Comparisons between the original prototype and the suggested new design structure via CAE technique under the guide of these two stiffness parameters show a great improvement on the maximal deformation of the machine structure under the action of cutting forces. Originality/value: – Through the proposed integrative examination of two structural parameters and the CAE technique, together with design experiences, an optimal CNC machine structure can be obtained.